Preoperative Diagnosis of Pancreatic Cystic Lesions: The Accuracy of Endoscopic Ultrasound and Cross-Sectional Imaging. Issue 8 (November 2015) - Jang, Dong Kee; Song, Byeong Jun; Ryu, Ji Kon; Chung, Kwang Hyun; Lee, Ban Seok; Park, Joo Kyung; Lee, Sang Hyub; Kim, Yong-Tae; Lee, Jae Young
Abstract : Objective: This study aimed to evaluate the accuracy of endoscopic ultrasound (EUS) and cross-sectional imaging including multidetector computed tomography (MDCT) or magnetic resonance imaging (MRI) as a preoperative diagnostic modality for the pancreatic cystic lesions. Methods: Three hundred eighteen patients with surgically proven pancreatic cystic lesions were enrolled as a study cohort from 1998 to 2011. Preoperative radiological, EUS, and final histopathologic diagnosis were correlated to measure several kinds of diagnostic performance. Results: A total of 318 patients underwent preoperative MDCT, with additional imaging modalities such MRI and/or EUS in 215 (67.6%) and 108 (34.0%) patients, respectively. κ Values among the different modalities were as follows: MDCT versus pathology = 0.52 ( P < 0.0001), MDCT + MRI versus pathology = 0.674 ( P < 0.0001), and EUS versus pathology = 0.558 ( P < 0.0001). The sensitivity and specificity in terms of ability to predict neoplastic cysts were as follows: MDCT, 83.1%/70.0%; MDCT + MRI, 94.7%/58.7%; and EUS, 88.5%/52.9%. The diagnostic accuracies of MDCT and MDCT + MRI were 61.4% (62/101) and 80.5% (173/215), respectively, and that of EUS was 70.4% (76/108). Conclusions: Magnetic resonance imaging as an additional diagnostic modality to MDCT increased the accuracy, sensitivity, and specificity, as well in terms of predicting neoplastic cysts.